2017
DOI: 10.1016/j.ibusrev.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foreign acquisitions on financial constraints, productivity and investment in R&D of target firms in China

Abstract: This paper examines whether foreign acquisitions lessen financial constraints, improve investment in research & development (R&D) and productivity of the target firms in Chinabased on a sample of 914 cross-border mergers and acquisitions (CBM&A) over the period of 1994-2011. Using investment to cash-flow sensitivity to measure financial constraints, we find that foreign acquisitions in China are associated with a reduction of target firms' financial constraints, irrespective of the ownership type of the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 89 publications
1
21
0
1
Order By: Relevance
“…For example, Ref. [7] analyzed the investment activities of Japanese firms with large publicly traded debt (corporate bonds) during the global financial crisis of 2008. It was found that firms with close bank-firm relationships are less financially constrained and have low borrowing costs.…”
Section: Literature Overview and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Ref. [7] analyzed the investment activities of Japanese firms with large publicly traded debt (corporate bonds) during the global financial crisis of 2008. It was found that firms with close bank-firm relationships are less financially constrained and have low borrowing costs.…”
Section: Literature Overview and Hypotheses Developmentmentioning
confidence: 99%
“…Regarding this measurement issue, we recommend for advance reading an overview by [21] on the literature related to measuring financial constraints. One stream of literature uses the data of financial statements and identifies the financial constraints indirectly-by means of sensitivity of investment costs to diverse factors [4,5,7,11].…”
Section: Literature Overview and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors have been proposed to affect the performance outcomes of acquisitions, including acquisition experience (Haleblian & Finkelstein, 1999;Vermeulen & Barkema, 2001), integration (Schweiger & Lippert, 2005), institutional variables (Brockman, Rui, & Zou, 2013), and the resources of acquirers and targets. This study focuses on the impacts of the acquirer and target resources on the success of acquisitions in emerging markets, as there is a pressing need to understand the dynamics of the acquisitions taking place in these markets (Chen, Hua, & Boateng, 2017;Liou, Rao-Nicholson, & Sarpong, 2018).…”
Section: Theoretical and Empirical Literature Reviewmentioning
confidence: 99%